Pertarungan Politik (Pemilihan Presiden dan Wakil Presiden Indonesia) Dalam Visual Meme - yoni sudiani; eva yanti; cameron malik (Jurusan Seni Rupa, Fakultas Bahasa dan Seni, Universitas Negeri Padang, 2019)
This study discusses the form of political battles that will be held in 2019, which are represented in the form of political memes. As a form of battle, the campaign team from each camp all members involved in the campaign team always have different strategies. For example, the Jokowi-Maaruf team puts forward a defensive strategy, they prefer to explain and clarify all forms of criticism made by the Prabowo-Sandi (PAS) team. Therefore, the visual memes made by Jokowi-Maaruf's team explained more about Jokowi's achievements during his tenure as president which manifest in visual meme that perform in visual communication media such as comics, infographics and posters. Likewise with the Prabowo-Sandi team, the strategies used are more likely to be the style of